Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.



$$\frac{1}{2^x} = \frac{5}{8^{x+2}}$$

My attempt:

$$\frac{1}{2^x} = \frac{5}{8^{x+2}}$$

$$\Rightarrow 5 \cdot 2^x = 8^{x+2}$$

$$\Rightarrow 2^{\log_2 5+x} = 8^{x+2} $$

$$\Rightarrow (\log_2 5 + x)(\log_a 2) = (x+2)(\log_a 8)$$

And then just keep going like this, but I'm obviously wrong already as the answer is:

$$ x = \frac{\ln 5 - 9 \ln 2}{2 \ln 2}$$

What am I doing wrong?

EDIT: If someone could enlarge the latex for me that would be great.

share|improve this question
you have a good start, but you can continue better. See my solution. –  Babak Miraftab Feb 21 at 20:13
You can get the larger displayed latex form by bracketing the math code between two pairs of dollar signs (insead of one pair of dollar signs). I just did this for your question. –  Dave L. Renfro Feb 21 at 20:17
Thank you for that! –  user3200098 Feb 21 at 20:21
With the content of the answers below, I'm not certain that the given answer is correct. Is there perhaps a copying error? –  abiessu Feb 21 at 21:41

4 Answers 4

up vote 2 down vote accepted

$2^{\log_2 5+x} = 8^{x+2}$ implies that $2^{\log_2 5+x} = 2^{3x+6}$ and so $\log_2 5+x=3x+6$. We can conclude that $x=\frac{\log_2 5-6}{2}$.

share|improve this answer
Thank you...!!! –  user3200098 Feb 21 at 20:20

Some of the answers don't mention that $8=2^3$. $$ 5\cdot 2^x = 8^{x+2} $$

Remember that $8=2^3$. So $$ 5\cdot 2^x = (2^3)^{x+2}. $$ $$ 5\cdot 2^x = 2^{3(x+2)} $$ $$ 5\cdot 2^x = 2^{3x+6} $$ $$ 5 = 2^{3x+6}\cdot 2^{-x} = 2^{2x+6} $$ $$ \log_2 5 = 2x+6 $$ $$ -6 + \log_2 5 = 2x $$ $$ \frac{-6+\log_2 5}{2} = x $$

share|improve this answer
Thanks a lot :) –  user3200098 Feb 21 at 22:47
I didn't realize I could do $5 = 2^{3x+6}\cdot 2^{-x} = 2^{2x+6}$ though. Multiply by negative exponent on both sides that is to get rid of the $2^x$ on one side. –  user3200098 Feb 21 at 22:52
@user3200098 : What is being done is this: $2^{3x+6}\cdot 2^{-x} = 2^{\Big(3x+6\Big)+\Big(-x\Big)}$. Then simplify $(3x+6)+(-x)$ to get $2x+6$. –  Michael Hardy Feb 22 at 0:34

With a slight modification, we have

$$5\cdot 2^x=8^{x+2}=(2^3)^{x+2}=2^{3x+6}$$

which means that

$$5=2^{2x+6}\\ \log_2 5=2x+6\\ x=\frac{\log_2 (5)-6}2$$

Transforming to the natural logarithm would look like

$$5=2^{2x+6}\\ \ln 5=(2x+6)\ln 2\\ x=\frac{\ln 5-6\ln 2}{2\ln 2}$$

share|improve this answer

HINT Use substitution to solve the equation easily $\to$ pose $2^x=t$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.